2022
DOI: 10.1002/adom.202200687
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics‐Controlled Interfacial Synthesis of Janus and Patchy Heterostructures Based on Perovskite Nanocrystals

Abstract: Heterostructures integrated by diverse material featuring nanocrystals (NCs) tunable properties and functions are of great interest. However, to rationally design and precisely control the heterostructures in multiple shapes still remains a tremendous challenge. In this work, the nucleation of SiO2 nanoparticles is manipulated via a kinetics‐controlled water–hexane interfacial reaction system to construct Cs3Cu2I5/SiO2 heterostructures, which can be well controlled in Janus and patchy morphology. In this inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…[27][28][29] For example, Zhao et al found that the luminescence of Cs 3 Cu 2 Cl 5 NCs cannot sustain under ambient atmosphere due to the oxidation of Cu + to Cu 2+ . 30 A similar situation was also observed in Cs 3 Cu 2 I 5 NCs 31 and Rb 2 CuBr 3 crystals. 32 Thus, suppressing the oxidation of monovalent copper ions is of great importance for maintaining the crystalline structure and luminescence properties.…”
Section: Introductionsupporting
confidence: 74%
“…[27][28][29] For example, Zhao et al found that the luminescence of Cs 3 Cu 2 Cl 5 NCs cannot sustain under ambient atmosphere due to the oxidation of Cu + to Cu 2+ . 30 A similar situation was also observed in Cs 3 Cu 2 I 5 NCs 31 and Rb 2 CuBr 3 crystals. 32 Thus, suppressing the oxidation of monovalent copper ions is of great importance for maintaining the crystalline structure and luminescence properties.…”
Section: Introductionsupporting
confidence: 74%
“…e–g) Reproduced with permission. [ 142 ] Copyright 2022, Wiley‐VCH. h) RL intensity of Cs 3 Cu 2 I 5 and Mn 2+ ‐doped Cs 3 Cu 2 I 5 at different temperature.…”
Section: Stability Of Tchsmentioning
confidence: 99%
“…[210][211][212][213][214][215] Despite most TCH materials present enhanced stability compared to the lead-based perovskites, the stability issue of TCHs is still an ongoing challenge due to their ionic properties similar to perovskites. [140,142] Recently, many research groups have experimentally and theoretically studied the influence of environmental conditions on the structural and optical characters of TCHs, and many methods including surface passivation and ion doping, have been developed to surmount the stability troubles of TCHs. In this section, we will introduce the previous reports about the inherent stability of various TCHs, and critically review the key strategies to enhance the stability of TCHs.…”
Section: Stability Of Tchsmentioning
confidence: 99%
See 1 more Smart Citation
“…CsPbX 3 NCs could be formed at the water/hexane interface, which may provide an opportunity for nanoparticle surface modification. Prof. Zhang's group 102,103 demonstrated an effective sol–gel process for modifying the surface of perovskite NCs at the interface of water/nonpolar solvents and producing highly stable monodisperse CsPbX 3 /SiO 2 and CsPbBr 3 /Ta 2 O 5 Janus NCs, exhibiting significantly enhanced PL stability against damage by air, water, and light treatment. Additionally, the reaction rate could be controlled by changing the ions' interfacial diffusion rate in such a bi-phasic interface.…”
Section: Interface Engineering Of Mhp Ncsmentioning
confidence: 99%